Surgical management of suspected gallbladder cancer: The role of intraoperative frozen section for diagnostic confirmation. Issue 3 (24th October 2021) - Chan, Benjamin K. Y.; Carrion‐Alvarez, Lucia; Telfer, Rebecca; Rehman, Adeeb H.; Bird, Nicholas; Mann, Kulbir; Jones, Robert P.; Malik, Hassan Z.; Fenwick, Stephen W.; Diaz‐Nieto, Rafael
Abstract: Background: Preoperative diagnosis for suspected gallbladder cancers is challenging, with a risk of overtreating benign disease, for example, xanthogranulomatous cholecystitis, with radical cholecystectomies. We retrospectively evaluated the surgeon's intraoperative assessment alone, and with the addition of intraoperative frozen sections, for suspected gallbladder cancers from a tertiary hepatobiliary multidisciplinary team (MDT). Methods: MDT patients with complex gallbladder disease were included. Collated data included demographics, MDT discussion, operative details, and patient outcomes. Results: A total of 454 patients with complex gallbladder disease were reviewed, 48 (10.6%) were offered radical surgery for suspected cancer. Twenty‐five underwent frozen section that led to radical surgery in 6 (25%). All frozen sections were congruent with final histopathology but doubled the operating time ( p  < 0.0001). Both the surgeon's subjective and additional frozen section's objective assessment, allowed for de‐escalation of unnecessary radical surgery, comparing favourably to a 13.0% cancer diagnosis among radical surgery historically. Conclusions: The MDT process was highly sensitive in identifying gallbladder cancers but lacked specificity. The surgeon's intraoperative assessment is paramount in suspected cancers, and deescalated unnecessary radical surgery. Intraoperative frozen section was a safe and viable adjunct at a cost of resources and operative time.